PENGAWASAN IZIN MENDIRIKAN BANGUNAN (IMB) (STUDI KASUS BANGUNAN RUMAH TOKO TAHUN 2017-2018 DI KOTA PEKANBARU) - G Novia Hermashinta Safitri; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Controlling Building Permit is one of the problems that often occurs in the city of Pekanbaru. Shophouse building owners are found to have no Building Permit. Although the government of Pekanbaru City gave authority to the One Stop Investment and Integrated Service Service to supervise the Shop Houses building, but the supervision of Building Construction Permits was still well implemented. The purpose of this study is to find out how the supervision of Building Shop Houses Permit for 2017-2018 in Pekanbaru City and the factors that become obstacles to the supervision. The theory used in this study is the Manullang theory which has an indicator that is setting standards, making judgments and making corrective actions. The research method used is a type of qualitative research with a case study method with data collection techniques through interviews, observation, and documentation. The selection of research informants used a purposive sampling technique. The results of this study indicate that there are factors that influence the Supervision of Building Permits for Shop Houses in Pekanbaru City. These factors are inadequate human resources and low community participation in building construction permits.Keywords : Controlling, Building Permit, Shophouse